The boat race - Geatches, Hazel (United Kingdom : Aardman Animations limited, 2021)
Does Timmy's boat win the race?
"The Boat Race" likely follows Timmy and his friends as they participate in a boat race. The story probably focuses on themes of friendship, teamwork, and the excitement of a friendly competition, tailored for beginner English readers. Location: 2A
Keywords: Boat race book